NAVIGATING THE DIGITAL LANDSCAPE: A SYSTEMATIC REVIEW OF DIGITAL MARKETING CAPABILITIES INTERRELATIONSHIPS - Gilang Pratama; Endang Ruswanti; Adilla Anggraeni (Jurnal Ilmu Manajemen (JIMMU), 2025)
AbstractThis study examines the role of Digital Marketing Capabilities (DMC) in enhancing business performance amid technological advancements and shifting consumer behaviors. Grounded in the Resource-Based View, it synthesizes existing literature to identify key themes and research gaps. The study informs both academic discourse and practical applications, emphasizing the strategic adaptation of marketing and highlighting the positive correlation between DMC and firm performance. A qualitative approach is employed through a Systematic Literature Review to synthesize research on DMC. The review systematically identifies, screens, and analyzes empirical studies based on predefined criteria. This process ensures a rigorous examination of existing knowledge, enhancing understanding and guiding future research directions. The study confirms a strong positive relationship between DMC and firm performance, demonstrating improved customer engagement, data-driven decision-making, innovation, and cross-channel integration as critical factors. Firms with superior DMC achieve enhanced marketing outcomes, such as increased customer loyalty and revenue growth. The Resource-Based View supports DMC as a source of competitive advantage, with factors like marketing capabilities, entrepreneurial orientation, and firm size moderating this relationship. This study uniquely synthesizes DMC research using an SLR, offering a novel perspective on its role in sustaining competitive advantage. It provides valuable insights for academia and practice, particularly in marketing strategy adaptation.